XPages extension library : a step-by-step guide to the next generation of XPages components - Hannan, Paul (IBM Press : Pearson PLC, 2012)
The XPages Extension Library's next-generation XPages controls make application development far more efficient, effective, scalable, and rewarding. With IBM® Lotus® Notes®/Domino® 8.5.3 and Upgrade Pack 1, IBM has incorporated powerful new capabilities and support. These components and technologies are now fully ready for even the toughest production challenges. XPages Extension Library is the first and only complete guide to Domino development with this library; it's the best manifestation yet of the underlying XPages Extensibility Framework. Complementing the popular Mastering XPages, it gives XPages developers complete information for taking full advantage of the new components from IBM. Combining reference material and practical use cases, the authors offer step-by- step guidance for installing and configuring the XPages Extension Library and using its state-of-the-art applications infrastructure to quickly create rich web applications with outstanding user experiences. Next, the authors provide detailed step-by-step guidance for leveraging the library's powerful new support for REST services, mobile and social development, and relational data. The book concludes by showing how to include Java code in Domino XPages applications - a great way to make them even more powerful. Coverage includes Automating deployment of XPages Extension Library throughout your IBM Lotus Notes/Domino or IBM XWork environment Integrating modern design patterns and best practices into Lotus Domino applications with drag-and-drop ease Incorporating AJAX capabilities with Switch, In Place Form, and other dynamic content controls Extending applications with Dojo widgets, popups, Tooltips, Dialogs, and Pickers Implementing state-of-the-art navigation and outlines Using Layout and Dynamic Views controls to painlessly modernize most Domino applications to XPages Quickly building mobile interfaces for existing applications Using social enablers to connect with social platforms and incorporate social features Integrating SQL datasources into XPages data-driven applications.